Usefulness of minimally invasive autopsy in the diagnosis of arboviruses to increase the sensitivity of the Epidemiological Surveillance System in Ceará, Brazil - Livia Mendes de Almeida; Deborah Nunes de Melo; Manuella Mendonça da Silva; Pedro Mansueto Melo de Souza; Fernanda Kézia de Sousa Silva; Tania Mara Silva Coelho; Shirlene Telmos Silva de Lima; Anacelia Gomes de Matos Mota; Renata Aparecida de Almeida Monteiro; Paulo Hilario Nascimento Saldiva; Geraldo Gileno de Sá Oliveira; Luciano Pamplona de Góes Cavalcanti (Epidemiologia e Serviços de Saúde, 2024)
Abstract Objective: To create a protocol for performing minimally invasive autopsies (MIA) in detecting deaths from arboviruses and report preliminary data from its application in Ceará state, Brazil. Methods: Training was provided to medical pathologists on MIA. Results: A protocol was established for performing MIA, defining criteria for sample collection, storage methods, and diagnoses to be carried out according to the type of biological sample; 43 MIAs were performed in three months. Of these, 21 (48.8%) arrived at the Death Verification Service (SVO) with arboviruses as a diagnostic hypothesis, and seven (16.3%) were confirmed (six chikungunya cases and one dengue case); cases of COVID-19 (n = 9), tuberculosis (n = 5), meningitis (n = 4), cryptococcosis (n = 1), Creutzfeldt-Jakob disease (n = 1), breast cancer (n = 1), and human rabies (n = 1) were also confirmed. Conclusion: The protocol implemented enabled identification of a larger number of suspected arbovirus-related deaths, as well as confirmation of other diseases of interest for surveillance.